(untitled) (Research, Society and Development, 2020)
The objective was to report a clinical case of gingival smile correction associated with passive eruption altered by means of gingivectomy in internal bevel and osteotomy with reverse planning and assisted by surgical guide developed to facilitate the technique, where did the questionnaire of OHIP and EVA to evaluate the improvement in quality of life and the pain in the postoperative period. A 23-year-old patient was dissatisfied with his smile, which had a high gingival exposure with short clinical crowns. In the clinical examination, an increase in bone volume was observed in the anterior region of the maxilla, thus diagnosing altered passive eruption. Before the surgical act was carried out the molding, to be done waxing from the data collected. After these steps, a surgical guide was developed, fenestrated with acrylic resin, following the planned measures, being able to guide the surgical incisions. After 21 days of the surgical procedure, the new measures were re-evaluated and compared with those stipulated in the preoperative planning, in which the increase in the clinical crown of the elements was 100% equal to the planned one, thus demonstrating the effectiveness of the guide surgical fenestration, improving the quality of life and providing minimal discomfort. Knowing that esthetics is closely linked to the quality of life of the individual, it is essential to use a predictable planning, using techniques such as diagnostic waxing and surgical guidance that provides a more reliable procedure.